PENGARUH GENDER DALAM INTERAKSI KELAS TERHADAP KEMAMPUAN LITERASI MATEMATIKA PADA MATA KULIAH LOGIKA MATEMATIKA - Nur Hasanah (STKIP PGRI Situbondo, 2024)
This study aims to examine the effect of gender in class interaction on the mathematical literacy abilities of first semester students of the mathematics education study program. The sampling technique in this study was random sampling based on consideration. The collected data were analyzed using a simple regression test, before carrying out the previous regression test, preparing instruments, namely questionnaires and interview instruments. After carrying out the research, the questionnaire was tested for validity and reliability first, then carried out a simple regression test which functioned to determine the effect of gender on mathematical literacy abilities. Gotthe results of the regression equation obtained Y = 54.179 + 0.442 X, this equation shows that the value of the regression coefficient for Gender (X) is positive, which means that every increase in the Gender variable has an influence on Mathematical Literacy (Y).